Impact of Economic and Noneconomic Factors on Inflow of Remittances into Bangladesh: Application of Robust Least Squares Method - Rahman, Md. Hasanur; Habib, Ahsan (Finance & Economics Review, 2021)
Purpose: Remittance plays an important role in the economy of Bangladesh. It also contributes to the change in the social structure and standard of living. The purpose of the study is to identify the economic and non-economic determinants of the remittance inflow into Bangladesh. Methodology: The study considered two types of variables as the determinants of the remittance inflow: economic and non-economic. Economic determinants of remittances inflows included exchange rate, education, economic growth rate, and market interest rate. The non-economic determinants covered control of corruption, government effectiveness, and political stability. Monthly data were used for the case of economic determinants from 2014 to 2020 and annual data were used in the case of non-economic determinants from 1996 to 2018. The marginal effect of each variable has been analyzed by using the Robust Least Squares (RLS) method. Results: The estimated results of this study state that, economic determinants like capital formation and education factors have a positive and significant impact on remittances inflows in both static and dynamic cases. However, the exchange rate does not create a positive impact due to volatility. The RLS estimation shows the control of corruption has a positive impact on remittances inflows whereas government effectiveness and political stability hurt remittances inflows in Bangladesh. Implications: The current study identified the significant determinates of remittances inflows in Bangladesh. The findings have implications for policy formulation as regard remittances and non-resident Bangladeshis.